Devlet mallarının haczedilmezliği - Çavuş Şahin, Büşra Gülnihal (My University, 2025)
Tarihsel süreç içerisinde insan haklarına verilen önemin bir yansıması olarak haciz sonucu borçluların temel haklarının zedelenmemesi amacı ile haczedilmezlik kuralları düzenlenmiştir. İİK m. 82/ 1-1 hükmünde yer alan devlet mallarının haczedilmezliği diğer bentlerden farklı olarak insan haklarını değil kamu yararını temin etme amacı güder. Bununla beraber devlet mallarının haczedilmezliği konusunda normun yeterince açık olmaması uygulamada bir takım sorunlara yer açmaktadır. İnceleme kapsamında haciz ve haczedilmezlik kurallarının amaçları incelenmiş; daha sonra devlet mallarının haczedilmezliğine dair kuralın haczedilmezlik düzenlemesinin getiriliş amacı, insan hakları ve devletin temel nitelikleri ile ilişkisi irdelenerek uygulamada ortaya çıkan problemlerin çözümü için öneriler getirilmiştir

As a reflection of the importance given to human rights in the historical process, the rules of non-forfeiture have been regulated in order not to damage the fundamental rights of debtors as a result of foreclosure. Article 82/ 1-1 of the Enforcement and Bankruptcy Code, unlike other articles of the EBC, aims to ensure public interest rather than human rights. However, the clarity in the norm regarding the non-seizure of state property leads to some problems in the interpretation of the provision. During this review, a preliminary research was conducted to determine the purposes of the confiscation and non-confiscation provisions. This was followed by an examination of the relationship between the non-appropriation rule and the non-appropriation regulation and human rights and the fundamental attributes of the state. Finally, recommendations were made to address the difficulties encountered in practice.
Non-confiscation of state property
Keywords: attributes of the state; devlet; Devlet malları; devletin nitelikleri; Executions (Law); Government property; haczedilmezlik; human rights; İcra-iflas hukuku; insan hakları; non-confiscation; state; Turkey; Türkiye